Angiotensin Converting Enzyme (ACE) Insertion/Deletion (I/D) Gene Polymorphism - Ejder Yildirim, Malik; Kocak, Nadir; Ozen, Filiz; Ozdemir, Ozturk (Annals of Medical Research, 2021)
None
Keywords: ACE, Insertion, Deletion, Polymorphism.